Keabsahan Pembuktian Ahli dalam Tindak Pidana Pencabulan Anak Oleh Ayah Kandung Pada Studi Putusan Nomor 22/JN/2021/MS.Aceh. - Indah Maria Maddalena Simamora; Rugun Romaida Hutabarat (LPPM Universitas Ekasakti Padang, 2023)
The validity in proving a crime must provide a strong belief to the judge about the truth of the evidence. This is in order to determine whether the defendant really committed the act charged or it can also be used to obtain the basis for the verdict in resolving a case. Expert testimony has the nature of validity or validity of evidence in assisting the examination in the crime of child abuse. The research will examine the validity of expert evidence in the crime of child molestation by the biological father. This study aims to determine how the validity of expert evidence in the crime of child molestation by biological fathers using descriptive-based normative juridical methods, using primary data, namely legislation, decisions and secondary data sourced from books, journals related to the validity of experts in the crime of child molestation. The problem examined in this study refers to one of the judge's considerations in Decision Number 22/JN/2021/Ms.Aceh. which states that the psychological expert is considered to have made every effort to lead the child victim to provide testimony according to the charges and the expert's testimony is ruled out. If there is doubt about the testimony presented by the expert, the Criminal Procedure Code provides room for the judge to call a second expert to be questioned to avoid in dubio pro reo in the judge's decision. If the child is a victim, the examination process must be accompanied by community counselors and social workers who have the competence and profession of social work and expertise. Based on this, expert evidence and psychological experts are needed in the examination of the crime of child abuse.